Vocational Training Team (VTT) Rotary Grant on Teaching Strategies and Conversational English at Secondary Schools in Tanzania, Africa - Thomas Walsh Jr; Hayley Nelson; Brian Borer; Gretchen Hanson (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2017)
The article describes the need for a staff development on effective teaching methodologies and English conversation for government schools in Tanzania.  Given this need a training program was provided and funded from Rotary Foundation and the Rotary Club of Ames District 6000 as a Vocational Training Team (VTT) grant.  Objectives of the program were to provide the training program on teaching strategies to staff including improving use of English through dialogue and using donated Amazon Readers with solar panels.  Discussion items of the article include development and authorization of the VTT grant with support from the Rotary Club of Moshi-Mwanga.  Descriptions of the schools selected for the project is provided along with a report by the training team about the implementation of the program at their campus site.  Evaluation of the training program using an interest survey, pre- and post-implementation survey, and post evaluation of the schools is discussed.  Information provided about the primary goal of the project to train two faculty or staff as instructional coaches to sustain use of teaching methodologies with secondary school staff members is presented.  Access to the development of the trainer texts is provided with reference of the curriculum used for previous projects in Tanzania and published with the AJOTE.